FEEDING PROBLEMS OF CHILDREN WITH AUTISM - Balikçi, Ozge Sultan; Çiyiltepe, Müzeyyen (PEOPLE: International Journal of Social Sciences, 2017)
Children with autism generally have feeding problems especially in their mealtime behavior. The purpose of this study is to identify the feeding problems of children with autism. To be able to determine the problems of children with autism BAMBI (Brief Autism Mealtime Behavior Inventory), (Demand, Johnson and Fokles, 2015; Meral and Fidan, 2014) is used. Twenty-one families of children with autism were participated in the study. The results of our study showed that according to the parental reports children with autism have feeding problems in terms of mealtime behavioral problems such as crying and yelling throughout meals. Other results of the study and recommendations are discussed in discussion.